An experimental study measuring the photon attenuation features of the P2O5–CaO–K2O–Na2O–PbO glass system. (November 2022) - Al-Ghamdi, Hanan; Sayyed, M.I.; Elsafi, M.; Kumar, Ashok; Al-Harbi, Nuha; Almuqrin, Aljawhara H.; Yasmin, Sabina; Khandaker, Mayeen Uddin
Abstract: Using an HPGe detector and multiradioactive point source ( 60 Co, 133 Ba, 137 Cs, and 241 Am), the photon attenuation properties of 40P2 O5 –20CaO–10K2 O-(30-x)Na2 O-xPbO (x = 0, 5, 10, 15, and 20 mol%) glasses were experimentally tested. The practical findings matched the theoretical results from the online XCOM program extremely well. It was shown that the linear attenuation coefficient may be utilized to assess the efficacy of photon protection as well as the effective atomic number, half-value layer, mean free pass, transmission factor, and radiation protection efficiency parameters. The chemical compositions of the glass system and the incident energies of the radiation source influenced all these factors. At low energies, the photon protection efficiency of the PCNKPb20 and PCNKPb15 samples was approximately 100%. Thus, these samples could block nearly all the low-energy radiation directed at them. The shielding competence was also compared to other recently reported commercial glasses. This shows that the PCNKPb20 glass can be an effective barrier against X-ray or gamma-ray radiation. Highlights: The photon attenuation properties of P2 O5 –CaO–K2 O–Na2 O–PbO glasses were reported. As energy levels rise, the shielding capacity of the glasses decreases. The HVL for PCNKPb20 and PCNKPb0 at 0.0595 MeV are 0.099 and 0.958 cm. PCNKPb20 glass can be an effective barrier against gamma-ray radiation.